1996
DOI: 10.1055/s-2007-1015717
|View full text |Cite
|
Sign up to set email alerts
|

Radiologisch assistierte perkutane Gastro-/Enterostomie - Retrospektive Analyse von 90 Eingriffen

Abstract: Radiologically assisted gastrostomies or enterostomies are a reliable and effective form of treatment even amongst difficult patients. The results and complications are comparable to those from endoscopic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
2
4
0
1
Order By: Relevance
“…Of these 91 patients, fluoroscopic-guided access was attempted by direct puncture of an effervescent-induced large gastric air bubble in 24 patients. Overall, the technical success rate in the current study was similar to or better than the rates reported in the literature for PRG, which varied between 85 and 100 % [6,13,14,[24][25][26]. The mean procedure time of the present study was shorter than the previously reported study by Wollman (33 min and 39 min for PRG and PEG, respectively) [6].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Of these 91 patients, fluoroscopic-guided access was attempted by direct puncture of an effervescent-induced large gastric air bubble in 24 patients. Overall, the technical success rate in the current study was similar to or better than the rates reported in the literature for PRG, which varied between 85 and 100 % [6,13,14,[24][25][26]. The mean procedure time of the present study was shorter than the previously reported study by Wollman (33 min and 39 min for PRG and PEG, respectively) [6].…”
Section: Discussionsupporting
confidence: 84%
“…In our study, 4.0 % of patients developed major AEs, including bleeding (n = 4), gastric tears (n = 1), intraabdominal abscess (n = 1), and colon injury (n = 1). Major AEs were reported for PRG between 5.9 and 20 % [6,13,14,[24][25][26], particularly peritonitis necessitating surgical treatment, gastric wall dissection/perforation, hemorrhage requiring transfusion, and gastrostomy metastasis. Although statistically not significant, our study shows such prevalence was smaller than other techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Since first described in 1981 [6], the percutaneous radiological gastrostomy has been proved to be safe and effective [1,18,19]. Success rates between 85% and 100% [14,18,20] have been reported for fluoroscopy guided techniques which are particularly feasible in challenging anatomic situations or after failed endoscopic gastrostomy attempts [20][21][22]. Our data confirm these data with high primary success rates of 98.3% and 92% for Pull-type-PRG and Push-type-PRG, respectively.…”
Section: Discussionsupporting
confidence: 81%
“…Mildenberger et al [12], in a mixed cohort of 90 percutaneous radiographic gastro-and enterostomies, indicate a mean fluoroscopy time of 12.6 minutes; however, almost 1/3 of these were distinctly complex duodenal or jejunostomies. In a comparison between PRG with and without gastropexy, Thornton et al [11] reported a fluoroscopy time of 4.73 minutes with gastropexy and 4.59 minutes without the procedure.…”
Section: Discussionmentioning
confidence: 99%